Do Students Know What They Think They Know?: Evaluating the Relationships between Online Practice Questions, Knowledge Monitoring, and Course Outcomes. Issue 4 (2nd October 2022) - Husmann, Polly R.; Smith, Theodore C.
Abstract: Previous research has shown the value of retrieval practice and metacognitive awareness for student success. The present research evaluated the use of online question modules, in relationship to examination and final course grades, to encourage the development of these skills in undergraduate anatomy. The results demonstrated trends in both questions completed and metacognitive awareness for final grades and grades on the first set of examinations. However, no association was found between the number of questions completed and the percent of questions on which the student was metacognitively aware. This suggests additional instruction or scaffolding is needed to improve these modules.